Carne Neemerranner — Telling Places and History on the Ground - Cameron, Patsy; Miller, Linn (The Australian Journal of Indigenous Education, 2009)
Abstract In the language of the Tebrikunna (Cape Portland) clan, Carne Neemerranneris “telling ground”. It is also what we call the research methodology designed for Meeting at Bark Hut, a recent community-engaged Aboriginal history project conducted in northeast Tasmania. The project examined, retraced and explored one brief, but poignant, episode in Tasmania's colonial contact history – a meeting between the parties of George Augustus Robinson, colonial agent charged with the “conciliation” and removal of Trouwunnan (Tasmanian) clanspeople from the Tasmanian mainland, and that most likely included Mannalargenna, one of the last Trouwunnan leaders still living in his own clancountry at the time (1830). While this episode and encounter has profound connotations for presentday Tasmanian Aborigines, its significance has largely been overlooked by academic historians. Meeting at Bark Hutwas conceived as an opportunity to redress this deficit, to allow the story of this event to be told and to come alive in a dynamic and culturally relevant way. This article offers some insight into the meaning and method of the project from both theoretical and practical perspectives.